Dating Abuse Prevention in Teens of Moms with Domestic Violence Protection Orders, North Carolina, 2010-2011 - Foshee, Vangie ([Verlag nicht ermittelbar], 2018)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed. Children exposed to domestic violence are at increased risk of experiencing and perpetrating violence against their partners when they become adolescents and adults. Despite this increased risk and the fact that approximately 15 million children are exposed to domestic violence yearly, there have been no evaluated dating abuse prevention programs conducted specifically with this population. The collection contains 2 SAS data files: baseline_final.sas (n=51; 465 variables) and followup_final.sas (n=32; 463 variables).